Nanomaterial Interfaces in Biology Methods and Protocols - Bergese, Paolo.; Bergese, Paolo.; Hamad-Schifferli, Kimberly.; Hamad-Schifferli, Kimberly. (Methods in Molecular Biology, 2013)
The intersection of nanotechnology with biology has given rise to numerous ideas for new ways to use nanotechnology for biological applications. Nanomaterials possess unique size- and material-dependent properties which make them attractive for improving regular biomedical fields, such as drug delivery, imaging, therapy, and diagnostics. Divided into three convenient sections, Nanomaterial Interfaces in Biology: Methods and Protocols covers protocols describing synthesis, fabrication, and construction of bio-nanomaterial interfaces, characterization protocols of bio-nanomaterial interfaces, and applications which utilize the bio-nanomaterial interfaces. Written in the highly successful Methods in Molecular Biology series format, chapters contain introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls.   Authoritative and accessible Nanomaterial Interfaces in Biology: Methods and Protocols will serve the new and emerging scientific community, enabling new capabilities and technologies that were not previously possible in medicine and biology.